Transformation of approaches of investment policy in the field of implementation of infrastructure projects in South Africa - A. A. Makarova (Модернизация, инновация, развитие, 2023)
Purpose: to study the current state and approaches of South Africa to the transformation of investment policy in the field of infrastructure projects in order to identify the results achieved and the prospects for ongoing reforms.Methods: general scientific methods were used in the study, in particular the analysis of statistics, the methods of deduction, analysis and synthesis. The sample of scientific studies and analytical materials on which the study is based draws on the work of scientists and experts on the topic in the region under study.Results: the assessment of the current state of the infrastructure sector of South Africa was carried out. The reasons for the need for reforms in the field of investment policy in order to stimulate the development of infrastructure in general and the implementation of infrastructure projects in particular were clarified, key directions for its transformation were identified. The tools being introduced were described and visually presented. An assessment of the results achieved to date was given.Conclusions and Relevance: the process of transformation of the investment policy of South Africa in the field of implementation of infrastructure projects is not yet complete. The achievement of all the goals set is hampered by both external factors, such as the consequences of the spread of the COVID-19 virus and others, and internal crises. Nevertheless, the attempts made by the state to increase the effectiveness of investment policy to improve the situation with infrastructure in the country have positive results. If the ongoing efforts are implemented to overcome the funding gap and solve problems associated with the low level of success of infrastructure projects, South Africa will not only be able to significantly improve the current situation in the infrastructure sector, but also significantly improve economic performance, which will undoubtedly have a positive impact on increasing the country's competitiveness.